Effect on EMG signal from upper limb muscle during conscious and subconscious perception - Fatin Zulaika, Hasan (2016)
The effect on EMG signal for upper limb muscle was investigated by two condition that is conscious and sub-conscious perception. There were six participants among University Malaysia Pahang’s students chosen as subjects. The subjects were asked to fix their arm in 90° isometric position and their data were recorded by two conditions and three times for each condition. The experiment was conduct by using shimmer EMG connect to the electrodes placed on subject’s muscle. The muscle chosen was forearms and biceps brachii. From the data recording, raw data was obtain and from the raw data, the Root Mean Square (RMS) and Mean Absolute Value (MAV) were calculated by using equation. The force exerted by each subject was recorded by using hand dynamometer. From RMS and MAV value, graph of mean, standard deviation and coefficient of variance were plotted after doing the calculation based on equation. As this project was comparing between conscious and sub-conscious, the results show that the highest EMG signal and muscle activation was during conscious condition. This show that during conscious condition, the electrical signal on upper limb muscle getting stronger.